Anthropogenic CO2 in the Philippine Sea, northwestern Pacific: Distribution, storage, and decadal variations. (September 2022) - Li, Cheng-long; Zhai, Wei-dong; Qi, Di; Zhang, Lin-lin; Zheng, Li-wen; Zhang, Yong
Highlights: Anthropogenic CO2 (CANT ) was investigated with details in the Philippine Sea. CANT storage increased 9–40% faster in the 2010 s than before. More than 82% of CANT storage in the tropical zone is input via ocean circulation. Abstract: The Philippine Sea, a deep tropical/subtropical marginal sea in the northwestern Pacific, is influenced by the Kuroshio Current in the west and the Kuroshio Recirculation (KR) in the north. In this study, the seawater carbonate system and related parameters were investigated along 130°/136°E and 21°N transects across the Philippine Sea in 2018–2019, and the inventory of anthropogenic CO2 (CANT ) was investigated with details. Results showed that the CANT inventory had a maximum value of 38.8 ± 0.6 mol m −2 at 25°−30°N (KR zone) and decreased southward to 27.8 ± 2.5 mol m −2 at 8°−15°N (tropical zone). In the tropical zone, more than 82% of the CANT inventory was input from extra-tropics through ocean transportation. On a decadal scale, the CANT inventory increased by 0.95 ± 0.10 mol m −2 yr −1 in the KR zone during the 2010s, which is 40% higher than that between 1994 and 2007 (∼0.68 mol m −2 yr −1 ). This acceleration is also higher than that predicted solely on the basis of increased atmospheric CO2 . In the tropical zone, however, the CANT inventory increased by 0.59 ± 0.08 mol m −2 yr −1 during the 2010s, which is similar to the rate between 1994 and 2007 (∼0.54 mol m −2 yr −1 ). This new high-quality dataset of carbonate system parameters could help the future quantification of the oceanic CANT inventory by increasing spatiotemporal resolution in the Philippine Sea.